(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Culture as defined by sociological theorists is perceived as a people`s way of life. This refers to the manner in which different people lead their daily lives from sunrise to sunset and repeats that every single day of their existence. In this respect, cultures tend to differ from one community to another, one region to the other, between countries, tribes, races and even in organizations. Culture in itself is not static but is always dynamic. Constantly changing to adapt itself to new trends. In the process adding to the existing practices new ones while also shading off the old ones which have since lost relevance. Generally cultural trends have been emerging and fading all at the same time. New trends come along and shapes cultural understanding while others emerge to reinforce the existing ones. Cultural researchers have often advocated that, in order to build a resilient and cohesive society, it is increasingly becoming important that individuals are exposed to the cultural trends and aim should be directed towards increasing awareness of cultural inclusivity as well as the detrimental impacts of cultural superiority. On the other hand, cultural superiority in employees tend to manifest itself in work enrolments characterized by multiculturalism. Such environment is dominated by individuals who have diverse origins. Cultural superiority in organization have been identified as a huge problem for most employee. However, the existence of these factor have never been given significant scholarly attention in terms of how such trends tend to impact human resources localization. It is the focus of this analysis to ensure that the existing gap in the literature is closed by ensuring that cultural superiority and localization of human resources is effectively analyzed. In order for the hypothesis relationship to be assessed, Andrew F. Hayes PROCESS V4.0 have been used. The focus is centered towards employees` cultural superiority behaviors and the effectiveness of localizing human resources. To achieve this mediator like employee knowledge-sharing tendency has been utilized. Employee cultural intelligence or the (CQ) has been used as a moderating mediator. The research utilized 400 respondents from diverse multinational company workers in China. The Analysis did establish that cultural superiority tendencies does impair effectiveness of knowledge-sharing potentials in an organization. This does impact human resources localization effectiveness in a negative way. In this respect, this analysis established that, cultural inclusiveness as a form of CQ has the impact of moderating mediated relationship that exist amongst employees in an organization.